Aminaphtone in the control of gingival bleeding in children - Pereira de Godoy JM; Macedo Paizan ML (Dove Medical Press, 2014)
José Maria Pereira de Godoy,1,2 Mara Lucia Macedo Paizan3 1Department of Cardiology and Cardiovascular Surgery, Faculdade de Medicina de São José do Rio Preto (FAMERP), São José do Rio Preto, 2Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq), Brasília, 3FAMERP, São José do Rio Preto, Brazil Aim: The objective of the current study was to evaluate the efficacy of aminaphtone to control gum bleeding.Patients and methods: Fifteen male and 15 female children, aged between 10 and 18 years with a mean age of 13.4 years and with gingival bleeding, were enrolled in this randomized, double-blind, placebo-controlled, Phase IV clinical trial. The inclusion criterion was gingivitis with gingival bleeding. Participants were prescribed either aminaphtone or placebo. Thirty identical boxes containing blister packs of identical pills of either aminaphtone or placebo were produced and coded with unique numbers by the manufacturer (Baldacci Laboratory, Brazil) and donated for this trial. A research assistant administered aminaphtone (Capilarema 75 mg) to fifteen patients or placebo to fifteen patients twice daily for 5 days. Intraoral clinical evaluations of bleeding were made before starting medication/placebo and then at 3 and 5 days after administration.Results: On comparing the number of bleeding points before and after treatment between the aminaphtone and placebo groups, we found significantly higher reductions with the medication (P<0.0001).Conclusion: Aminaphtone reduces gum bleeding in gingivitis, and may have a supportive role in the control of bleeding. Keywords: periodontitis, bleeding, treatment